1992
DOI: 10.1177/074823379200800403
|View full text |Cite
|
Sign up to set email alerts
|

History and Clinical Presentation of the Chemically Sensitive Patient

Abstract: Although no one has all the answers to the mystery of chemical sensitivity, the reality of this condition, most recently called multiple chemical sensitivities, is not in doubt. Evidence is increasing of its possible physiologic mechanisms, which will be discussed later in this volume. From the evidence and from personal and professional experience, the author believes that chemical sensitivity is not a diagnosis of exclusion, and that fixed-name diseases may have environmental triggers or complicating factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…effects of air aldehydes and VOCs (1-4) because of the increase of air tightness of recent buildings and houses in well-developed countries. MCS is caused by multiple chemical substances that are found not only in the outdoor environment, such as pesticides, but also in indoor air and which are similar to substances inducing SBS (5)(6)(7)(8). In addition, lowdose exposure to asbestos causes mesothelioma and represents a situation that includes adverse effects on health associated with indoor air circumstances since most asbestos is used in architectural materials for heat/fire resistance (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…effects of air aldehydes and VOCs (1-4) because of the increase of air tightness of recent buildings and houses in well-developed countries. MCS is caused by multiple chemical substances that are found not only in the outdoor environment, such as pesticides, but also in indoor air and which are similar to substances inducing SBS (5)(6)(7)(8). In addition, lowdose exposure to asbestos causes mesothelioma and represents a situation that includes adverse effects on health associated with indoor air circumstances since most asbestos is used in architectural materials for heat/fire resistance (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical samples studied by some authors (98)(99)(100)(101)(102) were also predominantly women. In their large representative household population study, Meggs et al (11) found that 39% of women and 24% of men reported chemical sensitivity.…”
Section: Gendermentioning
confidence: 99%
“…Because research on treatments for MCS is sparse, people have few data on which to rely when choosing interventions. Physicians have described health findings from patient samples (Bell et al 1995;Galland 1987;Heuser et al 1992;Lieberman and Craven 1998;Ross 1992a) and suggested treatment strategies (Jewett 1992;Ross 1992b;Ziem 1992), but only a small number of published studies describe MCS treatment and follow-up (Lax and Henneberger 1995). In addition, only three studies to date have examined patients' assessments of a large number of health interventions for MCS (Gibson 2000;Johnson 1996Johnson , 1997aJohnson , 1997bJohnson , 1998Leroy et al 1996).…”
mentioning
confidence: 99%